2023
DOI: 10.3389/fimmu.2023.1123200
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal colonization with Candida auris and mucosal immune response in mice treated with cefoperazone oral antibiotic

Abstract: Candida auris, an emerging multi-drug resistant fungal pathogen, causes invasive infections in humans. The factors regulating the colonization of C. auris in host niches are not well understood. In this study, we examined the effect of antibiotic-induced gut dysbiosis on C. auris intestinal colonization, dissemination, microbiome composition and the mucosal immune response. Our results indicate that mice treated with cefoperazone alone had a significant increase in C. auris intestinal colonization compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition, C. auris infection induces a significantly decreased number of IL-17A+ ILCs and IL-17F+ ILCs in skin tissue relative to C. albicans infection. However, using an intestinal mouse model of infection, we recently found that C. auris and C. albicans elicit similar levels of cellular adaptive immune responses in the intestine ( 29 ). Mice orally infected with C. auris but not C. albicans had increased fungal-specific IgA levels in their serum ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, C. auris infection induces a significantly decreased number of IL-17A+ ILCs and IL-17F+ ILCs in skin tissue relative to C. albicans infection. However, using an intestinal mouse model of infection, we recently found that C. auris and C. albicans elicit similar levels of cellular adaptive immune responses in the intestine ( 29 ). Mice orally infected with C. auris but not C. albicans had increased fungal-specific IgA levels in their serum ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, using an intestinal mouse model of infection, we recently found that C. auris and C. albicans elicit similar levels of cellular adaptive immune responses in the intestine ( 29 ). Mice orally infected with C. auris but not C. albicans had increased fungal-specific IgA levels in their serum ( 29 ). These results suggest that adaptive immune responses are Candida species specific and may differ in different host mucocutaneous niches such as the gut and skin.…”
Section: Discussionmentioning
confidence: 99%
“…C. auris, known to colonize the skin and found in human excrement, has the potential to infiltrate plumbing systems via skin shedding and fecal disposal, eventually arriving at wastewater treatment facilities [80]. It is, therefore, unsurprising that it has been identified in such facilities and sewage systems across multiple countries.…”
Section: Potential Urban Non-hospital Environmental Reservoirsmentioning
confidence: 99%